2020
DOI: 10.1016/j.matt.2020.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Superionic Conductivity by Turning on Anion Rotation at Room Temperature in Fast Ion Conductors

Abstract: A combination of the maximum entropy method and AIMD simulations demonstrates that polyanion [PS 4 ] 3À rotation is facile in the fast ion conductors b-Li 3 PS 4 and its Si-substituted analog, Li 3.25 Si 0.25 P 0.75 S 4 , but absent in the nonconductive phase, g-Li 3 PS 4 . The increased entropy upon the substitution of Si for P stabilizes the high-temperature rotor phase (b-Li 3 PS 4 ) at room temperature. Jointtime correlation analysis and AIMD simulations show that [PS 4 ]/[SiS 4 ] anion rotational dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
114
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(118 citation statements)
references
References 50 publications
4
114
0
Order By: Relevance
“…4d ). While similar behavior has been observed in lithium superionic conductors containing borohydride anions B 10 H 10 2− 32 , B 12 H 12 2− 33 , and BH 4 − 34 , and the sulfides β-Li 3 PS 4 and Li 3.25 Si 0.25 P 0.75 S 4 35 , this is the first observed instance of rotational motion of Cl − in a halide single ion conductor. It is important to note that while there is polyanionic rotation, there is no signature for Zr(Y)-Cl bond breaking (Supplementary Fig.…”
Section: Resultssupporting
confidence: 77%
“…4d ). While similar behavior has been observed in lithium superionic conductors containing borohydride anions B 10 H 10 2− 32 , B 12 H 12 2− 33 , and BH 4 − 34 , and the sulfides β-Li 3 PS 4 and Li 3.25 Si 0.25 P 0.75 S 4 35 , this is the first observed instance of rotational motion of Cl − in a halide single ion conductor. It is important to note that while there is polyanionic rotation, there is no signature for Zr(Y)-Cl bond breaking (Supplementary Fig.…”
Section: Resultssupporting
confidence: 77%
“…4d). While similar behavior has been observed in lithium superionic conductors containing borohydride anions B10H10 2-, 29 B12H12 2-, 30 and BH4 -, 31 and the sulfides β-Li3PS4 and Li3.25Si0.25P0.75S4 32 , this is the first observed instance of rotational motion of Clin a halide single ion conductor. It is important to note that while there is polyanionic rotation, there is no signature for Zr(Y)-Cl bond breaking (Fig.…”
Section: Mechanism For Enhanced Conductivitysupporting
confidence: 77%
“…They found that [PX 4 ] 3− rotation transiently widens the bottlenecks in the migration pathways, introducing dynamical frustration that facilitates Na + diffusion. A similar mechanism has also been suggested in crystalline thiophosphates by several other authors, generally based on correlation between enhanced [PX 4 ] 3− rotational mobility and cation diffusion upon chemical or structural modification [84,[89][90][91][92][93][94]. In addition to the crystalline phases, Smith et al demonstrated that significant coupling between cation diffusion and the anion motion can be present in the Li 3 PS 4 glass at low temperature [95].…”
Section: (A) Soft Modes and Rotational Disordersupporting
confidence: 61%